2014
DOI: 10.1016/j.psyneuen.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Approach and avoidance coping: Diurnal cortisol rhythm in prostate cancer survivors

Abstract: Psychological coping responses likely modulate the negative physiological consequences of cancer-related demands. This longitudinal, observational study examined how approach- and avoidance-oriented strategies for coping with cancer are associated with diurnal cortisol rhythm in prostate cancer (PC) survivors. Sixty-six men (M age=65.76; SD=9.04) who had undergone radical prostatectomy or radiation therapy for localized PC within the prior two years reported their use of approach and avoidance coping via quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…This is consistent with the common finding of higher psychological distress among younger women . Other studies showed that male cancer patients were more likely to use avoidant coping strategies, even though they were as distressed as women . Although avoidant coping has sometimes been associated with less psychological adaptation and worse physical functioning, it may also have a buffering effect at the end of life …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is consistent with the common finding of higher psychological distress among younger women . Other studies showed that male cancer patients were more likely to use avoidant coping strategies, even though they were as distressed as women . Although avoidant coping has sometimes been associated with less psychological adaptation and worse physical functioning, it may also have a buffering effect at the end of life …”
Section: Discussionsupporting
confidence: 88%
“…[33][34][35] Other studies showed that male cancer patients were more likely to use avoidant coping strategies, even though they were as distressed as women. [36][37][38] Although avoidant coping has sometimes been associated with less psychological adaptation and worse physical functioning, it may also have a buffering effect at the end of life. 7 In our sample, patients who were widowed were more likely to experience high death acceptance compared with singles.…”
Section: Demographic and Social Predictors Of Death Acceptancementioning
confidence: 99%
“…The number of consecutive sampling days among the seven studies involving mindfulness meditation ranged from 1 to 3 days, and all of these repeated the baseline measures at 1-8 months. Among the studies that had 1 day of sampling, findings indicated that Tai Chi Chih practice was associated with a lower cortisol AUC (Campo et al, 2015), a body-mind-spirit intervention was associated with steeper diurnal cortisol slopes and lower evening cortisol concentrations (F. H. Hsiao et al, 2012); and a mindfulness-based stress (Palesh et al, 2008;Tell et al, 2014) Flatter slope associated with greater tumor size and BMI (F. H. Hsiao et al, 2013Hsiao et al, , 2015) Slope correlated with clinical disease stage (Kim et al, 2012) Flattened slope predictive of early lung cancer death, advanced lung cancer stage, and poor Karnofsky performance score (Sephton et al, 2013) Flattened slope associated with decreased survival in ovarian cancer (Schrepf et al, 2015) Flatter slope associated with poorer sleep and perceptions of stress, health, and social support (Ho et al, 2013) Flatter slope associated with cancer-related avoidance coping (Hoyt et al, 2014) Steeper slope associated with improved fatigue (Schrepf et al, 2013) Normalized diurnal patterns observed in ovarian cancer survivors remaining disease free at 1 year posttreatment (Schrepf et al, 2013) Steeper slope associated with greater amplitude of plasma cortisol (Zeitzer, Nouriani, Neri, & Spiegel, 2014) Flattened slope associated with acute stress in BC survivors compared to healthy controls; slope trends toward normal over time (Couture-Lalande, Lebel, & Bielajew, 2014) Disrupted rest/activity cycles are associated with flattened diurnal cortisol rhythm (Dedert et al, 2012) Note. AUC ¼ area under the curve (total cortisol production); AUCg ¼ area under the curve with respect to ground (total cortisol production); AUCi ¼ area under the curve with respect to increase from baseline; BC ¼ breast cancer; BMI ¼ body mass index; BMS ¼ body-mind-spirit; CAR ¼ cortisol awakening response; CARauci ¼ cortisol awakening response as the area under the curve with respect to increase from baseline; CARi ¼ cortisol awakening response increase; MBSR ¼ mindfulness-based stress reduction; IL-6 ¼ interluekin-6; QOL ¼ quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…Other work has shown that perceived stress was associated significantly with emotional and physical well-being among AA and CA men who were newly diagnosed with PCa (Halbert et al, 2010). Perceived stress also had a significant independent association with cancer-related psychological distress (e.g., intrusive thoughts) among these men (Hughes Halbert et al, 2010); Hoyt et al showed that PCa patients who used avoidant coping strategies had a greater dysregulated cortisol response (Hoyt et al, 2014). Our recent research in a community-based sample of South Carolina residents has shown that social stress (e.g., isolation) is significantly greater among AA men compared to CA men; social stress such as isolation is highly and significantly correlated (r=0.65, P=0.001) with perceived psychological stress.…”
Section: Potential Causes Of Racial and Ethnic Disparitiesmentioning
confidence: 97%